Construction of sundials via vectors. Issue 4 (19th May 2019) - Johansson, B. Tomas
ABSTRACT: A method based on oblique projection is presented for construction of sundials. The derived formulas are classical, but usage of vectors and projections renders a coherent presentation rather than a number of special cases. The presented work is aimed to be useful for those taking a beginning module on vector algebra.